Audit Laporan Keuangan Pasca Sarbanes Oxley Act: Suatu Tinjauan Literatur - Roza, Husna (Akuntansi dan Manajemen, 2013)
The Sarbanes-Oxley Act was signed into law on July 30, 2002 by President Bush. The Act is considered as the most significant change to federal securities laws in the United States since the New Deal. The Act is also designed to review legislative audit requirements in order to protect investors which consequently could assist in improving the accuracy and reliability of corporate disclosures that encompasses issues such as establishing a public company accounting oversight board, corporate responsibility, auditor, independence, and enhanced financial disclosure. The Sarbanes-Oxley Act supports the internal control development. According to the act, internal controls must be reviewed and reported in the annual report. Finally, as indicated by Sarbanes-Oxley, this evolution of the internal control process has been reactive in nature and has brought some changes to some aspects of financial audit through external auditor.